Do as We Say: Funders’ Invisible Hold Over Research - Roemer M.S. Visser; Lesley E. Thomaszweki (Adult Education Research Conference, 2005)
This roundtable is an open discussion of the commercialization of academic work, namely how funders’ expectations have the possibility of driving research outcomes. By exploring the possible ramifications the expectations funders have of our research outcomes, we can avoid contributing to the increasing commercialization of research